O conceito de Aufhebung em Hegel : uma investigação sobre a doutrina do ser na ciência da lógica e na enciclopédia - Albuquerque, Rosmane Gabriele Varjão Alves de (2021)
The present research aims to investigate the concept of Aufhebung [sublation] in Hegel (1770- 1831). The concept appears in a particularly relevant way in the final part of the “quality” moment of the Doctrine of Being, in the books that Hegel dedicated to Logic. Hegel wrote two books on Logic: the Science of Logic of 1812-1816, and the first volume of the Encyclopedia of Philosophical Sciences in Outline, of 1817. In the Science of Logic, specifically in the Doctrine of Being, Hegel separates a part entitled “Observation” to briefly address the term Aufhebung and its concept. It is in this context that Hegel reflects most on the expression. Apparently, this occurs as a result of an explanatory need regarding the term, demonstrating its possible difficulties. Thus, when demonstrating the problems related to the concept of Aufhebung worked by Hegel himself, there is a need for an investigation, which seeks to clarify what its difficulties are and how they can be overcome. In the doctrine of being, being, nothing and becoming are presented as systematic categories of speculative logic. The concept of Aufhebung appears as a necessary condition for the unfolding of logic. It is what makes each category move to another. Therefore, in becoming, sublation is a movement that suspends or raises all other categories, allowing the transition from one state to another. Thus, we present as a hypothesis that the concept of Aufhebung can be clarified in light of the problems related to the concept of becoming, present in the Science of Logic - Doctrine of Being - and in the Encyclopedia. In the development of the research, we analyzed the question of the philosophical method in Hegel, in order to present what he understands by logic and its main characteristics, important in the difference in relation to formal logic. We also approach the absolute form, which appears throughout his system. Then, we deepen the question of the dialectic of being-nothing-becoming and its relation with the concept of Aufhebung. Finally, we deal with the modality of contingency and necessity in dialectical logic and the problem of the beginning in Hegel.